Seminar On The Use Of Social Media For Business Promotion In The Digital Economy Era - Nurmuhlisa; Joni Rokhmat (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2025)
The seminar with the theme "The Utilization of Social Media for Business Promotion in the Digital Economy Era" was held as part of the Teaching Assistance Group Work Program of SMAN 5 Mataram in 2025. This seminar aims to provide students with an understanding of opportunities and strategies for the use of social media as a means of business promotion in facing the development of the digital economy. Participants in the activity are student representatives from classes X to XII. The implementation of the seminar was carried out through the delivery of material using presentation media and interactive discussion sessions. The results of the activity showed that participants gained insight into how to find business ideas in the digital era, basic strategies to promote products through social media, as well as challenges and solutions in the digital promotion process. This activity is expected to increase students' digital literacy, foster entrepreneurial interest, and motivate the younger generation to utilize technology productively towards a Golden Indonesia 2045.